PERILAKU MEROKOK REMAJA DI KECAMATAN KANDANGAN: STUDI KUALITATIF TENTANG PERAN KELUARGA DAN TEMAN SEBAYA - Okta Reza, Nia; Iqbal Birsyada, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Smoking behavior among adolescents continues to increase and has become a very serious public health problem, including in suburban areas such as Kandangan District, Temanggung Regency. This study aims to explore in depth the role of the family environment and peer groups in shaping and perpetuating smoking behavior in adolescents. Using a qualitative method with a case study approach, this data was collected through in-depth interviews with seven active adolescent smokers aged 15–18 years in Kandangan District, as well as environmental observations. The results show that the family acts as an "initial trigger" through visual normalization (seeing family members smoking) and weak supervisory control. Meanwhile, peer groups function as "accelerators and maintainers" of this behavior through the mechanisms of social pressure (peer pressure) and the need for group recognition. The negative synergy between family permissiveness and strong social solidarity is a major factor in smoking behavior among adolescents in this area. Results.Qualitative findings highlighted factors influencing smoking behavior in school adolescents. Negative family environment, negative peer environment, and easy cigarette accessibility contribute to smoking tendencies, while the school environment provides a more conducive and positive atmosphere for adolescents. In addition, exposure to anti-smoking advertisements containing information on the dangers of smoking is more impactful and better received by school adolescents than pro-smoking advertisements and promotions. Conclusion: The importance of the role of family, peers, and cigarette accessibility in preventing smoking behavior in adolescents. Interventions that focus on these factors are urgently needed to reduce the prevalence of smoking among adolescents.